EU and ASEAN : in common disunity - Chong, Alan (2020)
Nationalist obsessions and failure to grasp the transboundary ramifications of the COVID-19 pandemic characterise the deficient responses of the world’s two leading regional organisations. Serious reputational damage has been inflicted on the European Union and ASEAN.